Social networks and policy coherence: Administrators’ Common Core and teacher evaluation advice networks - Stosich, Elizabeth Leisy; Hatch, Thomas; Hill, Kathryn; Roegman, Rachel; Allen, David (Education Policy Analysis Archives, 2021)
In this study, we aim to deepen understanding of what it would take to develop the relationships, common understandings, and collective expertise that might support district-wide improvement efforts by examining the implementation of the Common Core and a teacher evaluation policy. Drawing on three years of social network data in three districts, we find that administrators were more likely to be talking together about teacher evaluation than the Common Core. Further, administrators with more positive views of the potential impact of these policies and their access to the human and technical resources necessary for implementation were more likely to engage in positive information seeking behaviors. These findings have important implications for policies intended to increase instructional coherence in schools and districts.